Synthesizing National Zakat Index Application In Indonesia - Sulistyowati, Sulistyowati; Rahmi, Asri Noer (Universitas Islam Indonesia, 2018)
The study aims to synthesize the implementation of National Zakat Index (NZI) in Indonesia that published by National Zakat Agency (Baznas) on 2016. NZI is a model that attends the concept of multi-stages composition index that can compute all aspects of zakat comprehensively covering all stakeholders of zakat management starting from muzakki, mustahik, regulations and government budgets related to zakat on the macro and micro dimensions (Beik, 2016). This study is qualitative research which were used primary data through in-depth interviews and also secondary data through literature reviews. The results shows that the implementation of NZI throughout three years ago was effective which appropriate to the goal for measuring the effectiveness of zakat role in eradicating poverty. Furthermore, the synthezising stage conducted the proposed concept to encourage formed of integrated indexing model between Zakat and Waqf namely National Zakat-Waqf Index (NZWI). It is an idea that both of main Islamic financial instruments with the same final goals which are alleviating poverty and enhanching social welfare should engaged together as a unity into one harmony for better Indonesia. Moreover, advanced research is needed which is focus on practical aspects with considers other detail support elements.